International Conference on Intelligent Sensing and Information Processing, 2004. Proceedings Of
DOI: 10.1109/icisip.2004.1287637
|View full text |Cite
|
Sign up to set email alerts
|

Gabor filters for document analysis in indian bilingual documents

Abstract: Reasonable success has been achieved at developing mono lingual OCR systems in Indian scripts. Scientists, optimistically, have started t o look beyond. Development of bilingual OCR systems and OCR systems with capability t o identify the text areas are some of the pointers to future activities in Indian scenario. T h e separation of text and non-text regions before considering t h e document image for OCR is a n important task.In this paper, we present a biologically inspired, multichannel filtering scheme fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Dhanya et al [14], has achieved better performance in the latter method rather than the Pati et al [24]. But this would fail for some English characters which are descender dominant.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Dhanya et al [14], has achieved better performance in the latter method rather than the Pati et al [24]. But this would fail for some English characters which are descender dominant.…”
Section: Related Workmentioning
confidence: 99%
“…In the work of Pati et al [24] script recognition in bilingual document script (between Tamil and English) was performed using Gabor filters. Dhanya et al [9], has performed script classification using Gabor filters for bilingual document images in frequency domain.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have been conducted in the literature for page layout analysis using the multi-channel Gabor filters [43,38,44], while few ones have explored Gabor filters for ancient document image segmentation. For instance, Ribeiro et al proposed an optical character recognition system for ancient document recognition by applying fuzzy methods on aligned oriented features extracted using Gabor filters in the training step [45].…”
Section: Gabor Featuresmentioning
confidence: 99%
“…So, whatever the method is, our tests have shown that these methods are not robust to the variability of our corpus. That's why, we have decided like [8,9] to use texture-based approaches. Gabor filters, autocorrelation function, fractal or wavelet analysis are interesting methods because they allow a text/graphic separation without using any kind of structural information.…”
Section: Evaluation Of the Existing Methods On Ancient Booksmentioning
confidence: 99%